2020
DOI: 10.1177/0961203320936748
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in systemic lupus erythematosus according to cardiac magnetic resonance tissue characterization: clinical and echocardiographic features

Abstract: Objectives To determine the prevalence of myocardial injury (MInj) in systemic lupus erythematosus (SLE) according to cardiac magnetic resonance (CMR) criteria. To compare clinical and echocardiographic features of patients with and without MInj and identify predictors of myocardial tissue characteristics according to CMR. Methods SLE inpatients underwent CMR screening for MInj based on the Lake Louise Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…We also found that LGE positivity in the LV wall was associated with LV GLS and PDGLSR, and the latter had an independent correlation. du Toit et al (30) recently found that the LV GLS based on speckle-tracking echocardiography may be an independent predictor of the presence of LV LGE in SLE patients, which represents fibrosis/necrosis and potentially less reversible myocardial injury. The impaired LV GLS represents the longitudinal fibrous systolic dysfunction located predominantly in the sub-endocardium (10,31), confirming past reports of early SLE being prone to endocardial microvascular injury and diffuse myocarditis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that LGE positivity in the LV wall was associated with LV GLS and PDGLSR, and the latter had an independent correlation. du Toit et al (30) recently found that the LV GLS based on speckle-tracking echocardiography may be an independent predictor of the presence of LV LGE in SLE patients, which represents fibrosis/necrosis and potentially less reversible myocardial injury. The impaired LV GLS represents the longitudinal fibrous systolic dysfunction located predominantly in the sub-endocardium (10,31), confirming past reports of early SLE being prone to endocardial microvascular injury and diffuse myocarditis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine patients were included in the original cohort. 16 Three patients were lost to follow-up while ten patients died during the follow-up period. Mortality was related to SLE in two patients (neuropsychiatric SLE [NPSLE] and lupus nephritis [LN]) while five patients died due to infection related complications.…”
Section: Resultsmentioning
confidence: 99%
“…Between August 2016 and May 2018, all hospitalised SLE patients fulfilling the 2012 Systemic Lupus International Collaborating Clinics Classification (SLICC) criteria were screened for inclusion. 15,16 Exclusion criteria included existing myocarditis, cardiomyopathy (CMO), coronary artery disease, valvular/congenital heart disease and contraindications to undergo CMR (magnetic factors; contra-indications to gadolinium contrast). 17,18 Inflammatory skeletal myopathy co-existing with myocarditis limits the application of the LLC, thereby excluding these patients from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Moreover, a cardiac magnetic resonance (CMR) study showed that subclinical myocardial injury often exists in patients with SLE. 29 Myocardial injury is mainly characterized by fibrosis of the LV middle wall myocardium, which is not associated with the duration or severity of SLE. Extensive late gadolinium enhancement was found in patients with SLE who underwent CMR, which was attributed to the effects of aging.…”
Section: Discussionmentioning
confidence: 99%